Pengaruh Model Pembelajaran Contextual Teaching And Learning (CTL) Terhadap Hasil Belajar Siswa Kelas IV SDN Murtajih 1 Pada Mata Pelajaran Matematika Materi Luas Bangun Datar - Melly Yulia Utami; Ana Naimatul Jannah (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
The purpose of this study was to determine the significant effect of the Contextual Teaching and Learning model on the learning outcomes of class IV students at SDN Murtajih 1 in the mathematic subject area of flat shapes. This study uses quantitative methods with a Pre-Experimental Design and One Group Pretest-Posttest Design model. The sample was 23 students using the Total Sampling technique. Data collection used test instruments for student cognitive learning outcomes and teacher activity observation sheets. Based on the paired simple t-test, tcount 15.495 > ttable 2.073 shows that Ho is rejected and Ha is accepted or there is a significant effect of the Contextual Teaching and Learning model on the learning outcomes of class IV students at SDN Murtajih 1 in the Mathematic subject area of flat shapes. Based on the N-Gain test, the influence of the effect was 61.52%. The application of the Contextual Teaching And Learning model in mathematics learning about the area of flat shapes in class IV at SDN Murtajih 1 took place over 2 meetings with a duration of 70 minutes for each meeting and was carried out very well with an average implementation percentage of 100%.